ANTI-INFLAMMATORY STUDY OF ANREDERA CORDIFOLIA LEAVES AND CENTELLA ASIATICA HERBS AND ITS COMBINATIONS USING HUMAN RED BLOOD CELL-MEMBRANE STABILIZATION METHOD - Sutrisno, Entris; Adnyana I, Ketut; Yulinah Sukandar, Elin; Fidrianny, Irda; Aligita, Widhya (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Inflammation is body reactions in response to tissue injury and infection. In 2011, non-steroidal anti-inflammatory drug (NSAID) was the highest demand drug in Indonesia. However, long-term treatment using NSAID can cause several side effects to cardiovascular and digestive system. This research aimed to investigate anti-inflammatory properties of binahong leaves (Anredera cordifolia) and pegagan herbs (Centella asiatica). Methods: Ethyl alcohol extract of A. cordifolia leaves and C. asiatica herbs was evaluated for its anti-inflammatory properties using human red blood cell (RBC) – membrane stabilization assay. The extract concentrations used in this study was 100, 200, 400, and 800-ppm, and apigenin and asiaticoside concentration were 1, 2, 3, 4, 5, 6, 10, and 100 ppm. Diclofenac natrium (DN) was used as a standard drug. Results: The results showed that A. cordifolia extract (ACE) alone, C. asiatica extract (CAE) alone, and the combination of ACE and CAE could inhibit the hemolysis of RBC in hypotonic solution. The optimum concentration for ACE alone was 100 ppm; for CAE alone was 400 ppm; and for the combination of ACE and CAE was 50 ppm and 50 ppm, respectively. Apigenin and asiaticoside in concentration of 1-10 ppm showed more than 97% inhibition of hemolysis. DN as a standard drug showed optimum inhibition at concentration of 400 ppm. Conclusion: The ethyl alcohol extract of A. cordifolia leaves and C. asiatica herbs showed anti-inflammatory activity, both as a single treatment or as combinations, and apigenin and asiaticoside were responsible for anti-inflammatory activity in C. asiatica. Keywords: Anti-inflammation, Human red blood cell – membrane stabilization, Anredera cordifolia, Centella asiatica.